APAKAH TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DAPAT MEMITIGASI GANGGUAN TERHADAP LAPANGAN KERJA SELAMA PANDEMI COVID-19? BUKTI DARI KABUPATEN-KOTA DI INDONESIA - Wulansari, Indica (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
Limited research has been conducted on the effects of Information and Communication Technology (ICT) on employment resiliency during the COVID-19 pandemic, which is a relatively recent phenomenon. Therefore, this research aims to contribute to the current body of knowledge by utilizing district-level data in Indonesia, whereas most prior studies have used country-level data. Furthermore, this research utilizes several proxies for ICT penetration (internet penetration, mobile phone penetration, and internet speed). These proxies can potentially bolster the significance of this study to previous studies. This analysis, which utilized panel data regression, demonstrated that the COVID-19 pandemic can increase unemployment. Furthermore, in terms of resistance to the COVID-19 pandemic, employment are more resilient in districts with more sophisticated ICT penetration. Moreover, based on this study, the Government can concentrate on enhancing the districts that remain below the threshold regarding internet penetration, mobile phone penetration, and internet speed as priority areas for development.